A fluorine-removing resin grafted with rare metal active groups

By grafting rare metal active groups in the fluoro-removing resin, using lanthanum and chitosan coordinate chelating and zirconium oxide-loaded concave and concave rod soil, combined with cross-link polymerization technology of modified polyolefin microspheres, the existing fluoro-removing resin has been solved, and the existing fluoro-removing resin has low adsorption capacity and low selectivity when treating high concentration fluoro-containing wastewater, achieving efficient and stable fluoro-ion adsorption and long-life recycling.

CN119186523BActive Publication Date: 2025-04-15BENGBU TIANXING ION-RESIN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411542934.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-15
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

When existing fluorine-depleting resins treat fluorine-containing wastewater with high concentration and complex components, they have low adsorption capacity, low selectivity, difficult regeneration and short service life.

Method used

Modified chitosan is prepared by grafting rare metal active groups by chelating lanthanum and chitosan, and the modified concave and convex rod soil is loaded with zirconium oxide, combined with modified polyolefin microspheres to promote cross-link polymerization, and form a multi-particle cross-link polymerization structure.

Benefits of technology

The selective adsorption capacity and adsorption capacity of fluorine ions of fluorine-removing resins are significantly improved, the recycling service life of the resin is extended, and chemical and thermal stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186523B_ABST
    Figure CN119186523B_ABST
Patent Text Reader

Abstract

The invention discloses a defluorination resin grafted with rare metal active groups, belongs to the technical field of defluorination resins, and is used to solve the technical problems of low adsorption capacity, low selectivity, difficult regeneration and short service life of the defluorination resin in the prior art; the invention comprises the following components in parts by weight: 45-50 parts of modified attapulgite, 28-32 parts of modified chitosan, 18-22 parts of modified polyolefin microspheres and 60-80 parts of glutaraldehyde. The invention uses the modified polyolefin microspheres as a skeleton and glutaraldehyde as a cross-linking agent to promote the cross-linking polymerization of the modified chitosan and the modified attapulgite in an emulsified system to prepare a multi-particle cross-linked polymerized defluorination resin with high selective adsorption of fluorine, which not only effectively improves the adsorption capacity of the defluorination resin for fluorine in wastewater, but also improves the recycling regeneration ability of the defluorination resin, and prolongs the recycling service life of the defluorination resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorine-removing resins, and in particular to a fluorine-removing resin grafted with rare metal active groups. Background Art

[0002] With the acceleration of industrialization, the discharge of fluoride-containing wastewater has become increasingly prominent, posing a serious threat to the environment and human health. Fluoride has become a difficult problem to be solved in wastewater treatment due to its high toxicity and difficulty in degradation. At present, fluoride pollution exists to varying degrees all over the world. Part of the pollution comes from the erosion of underground fluoride-containing rocks by natural groundwater, and the other part comes from wastewater and waste gas discharged from human production and life. The fluorine in chemical wastewater comes from high-fluorine groundwater used in industry and coal coking, gasification and other processes. Due to the extremely strong activity of fluorine, excessive fluorine in chemical wastewater will cause great harm to the environment.

[0003] In the prior art, a Chinese invention patent with publication number CN117563685A discloses a high-efficiency defluoridating agent for wastewater and a preparation and use method thereof, wherein ethylene, styrene, a peroxide initiator and a polymerization catalyst are added to a reaction container pre-filled with a solvent for polymerization reaction to prepare a prepolymer liquid with a polymer molecular weight of 200 to 300, and the prepared enamine monomer and a cross-linking agent are added to the reaction container at the same time. After the reaction time is over, the heating is stopped and the reaction system is cooled, and the reaction product is post-treated and post-dried and granulated to obtain an ion exchange resin defluoridating agent. The ion exchange resin defluoridating agent of the present invention has high selectivity for fluoride ions and large adsorption capacity. In the preparation method, a low molecular weight prepolymer is first prepared to ensure that there are enough short straight chains in the resin to form support, and the porosity of the obtained resin is adjusted to obtain a suitable cross-linking density and ion exchange group density to ensure the resin's ability to absorb fluoride ions.

[0004] However, the defluorination resins disclosed in the prior art mainly improve the adsorption capacity of fluoride ions by introducing specific functional groups or ion exchange groups. However, these resins often face problems such as low adsorption capacity, low selectivity, difficulty in regeneration and short service life in practical applications. In particular, when treating high-concentration and complex fluoride-containing wastewater, its defluorination effect is difficult to meet actual needs.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a defluorination resin grafted with rare metal active groups, which is used to solve the technical problems of low adsorption capacity, low selectivity, difficult regeneration and short service life of the defluorination resin in the prior art.

[0007] The purpose of the present invention can be achieved through the following technical scheme: a defluorination resin grafted with rare metal active groups, comprising the following components in parts by weight: 45-50 parts of modified attapulgite, 28-32 parts of modified chitosan, 18-22 parts of modified polyolefin microspheres and 60-80 parts of glutaraldehyde.

[0008] Furthermore, the preparation method of the defluorination resin is as follows: modified attapulgite, modified chitosan, modified polyolefin microspheres, and emulsion are added to a reactor and stirred, sodium hydroxide solution is added dropwise to the reactor, the pH of the system is adjusted to 9-10, the temperature of the reactor is increased to 50-60°C, glutaraldehyde solution is added to the reactor, the reaction is kept warm for 4-6 hours, petroleum ether is added to the reactor, the reaction is kept warm and stirred for 30-50 minutes, and the defluorination resin is obtained by post-processing.

[0009] The synthetic reaction principle of fluorine removal resin is:

[0010] In an alkaline environment, it can promote the deprotonation of functional groups such as hydroxyl and amino groups, increase their nucleophilicity, and thus promote the occurrence of cross-linking reactions. Then, using glutaraldehyde as a cross-linking agent, the aldehyde group of glutaraldehyde reacts with other active groups such as amino groups on modified attapulgite, modified chitosan, and modified polyolefin microspheres to form a fluorine-removing resin with a three-dimensional cross-linked network structure and abundant active groups.

[0011] Furthermore, the dosage ratio of the modified attapulgite, emulsion and petroleum ether is 45-50g:700mL:1400mL, the mass fraction of the glutaraldehyde solution is 50%, the concentration of the sodium hydroxide solution is 2-3mol / L, and the emulsion is composed of toluene, tetrahydrofuran, purified water, polyethylene glycol 400, OP-20, and Tween-80 in a dosage ratio of 40mL:40mL:30mL:10g:3g:2g. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol 5 times, and then washed with deionized water 3 times, dried, and the filter cake is transferred to a drying oven at a temperature of 55-65°C, and vacuum dried to constant weight to obtain a defluorination resin.

[0012] Further, the modified polyolefin microspheres are processed by the following steps:

[0013] A1. Add glycidyl methacrylate, p-divinylbenzene, initiator and toluene into a reaction kettle and stir. Raise the temperature of the reaction kettle to 70-80° C., keep the temperature for 6-8 hours, and then lower the temperature to room temperature to obtain a polyolefin reaction liquid.

[0014] A2, add the emulsified solution into the reactor, stir rapidly at room temperature, add the polyolefin reaction solution dropwise into the reactor, and after the addition is complete, keep warm and stir for 30-50 minutes, and perform post-treatment to obtain polyolefin microspheres;

[0015] A3. Add gulose, purified water and sodium hydroxide into a reactor, stir until the system is dissolved, add polyolefin microspheres into the reactor, increase the temperature of the reactor to 50-60° C., keep the temperature for 2-3 hours, and post-treat to obtain modified polyolefin microspheres.

[0016] The synthetic reaction formula of modified polyolefin microspheres is:

[0017]

[0018] Where:

[0019]

[0020] The synthetic reaction principle of modified polyolefin microspheres is:

[0021] In the emulsified system, polyolefin reaction monomers are dispersed in the emulsified solution in the form of droplets by stirring. Under the action of a free radical initiator, glycidyl methacrylate and p-divinylbenzene monomers in the droplets are polymerized. Due to the isolation of the droplets, the polymerization reaction in each droplet proceeds relatively independently to form microspheres. As the polymerization reaction proceeds, the polymer chain in the droplet continues to grow and eventually forms solid microspheres. Gulose is a monosaccharide with multiple hydroxyls. Under the alkaline condition of sodium hydroxide, the hydroxyls of gulose are partially or completely deprotonated to form oxygen anions with strong nucleophilicity, which can undergo nucleophilic substitution reaction with the alkylene oxide groups on the polyolefin microspheres. During the reaction, by controlling the excessive use of gulose, polyhydroxyls and aldehyde modifications are formed on the outside of the polyolefin microspheres to prepare modified polyolefin microspheres.

[0022] Further, in step A1, the amount ratio of glycidyl methacrylate, p-divinylbenzene, initiator and toluene is 5g:4g:0.1g:50mL, and the initiator is azobisisobutyronitrile; in step A2, the volume ratio of the emulsified solution and the polyolefin reaction solution is 2:1, and the emulsified solution is composed of ethanol, purified water, polyethylene glycol, sodium dodecyl sulfate, and Tween-80 in an amount ratio of 50mL:30mL:3g:2g:2g, and the post-treatment includes: after the reaction is completed Afterwards, the filter cake was filtered, washed with anhydrous ethanol for 3 times and then dried, and the filter cake was transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain polyolefin microspheres; in step A3, the amount ratio of gulose, purified water, sodium hydroxide and polyolefin microspheres is 3g:30mL:2g:5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain modified polyolefin microspheres.

[0023] Further, the modified attapulgite is processed by the following steps:

[0024] B1. Add sodium hydroxide and deionized water to a reactor, stir at room temperature until the system is dissolved, add attapulgite to the reactor, increase the temperature of the reactor to 70-80°C, keep stirring for 2-3 hours, lower the temperature of the reactor to room temperature, let it stand for aging for 20-24 hours, and post-treat to obtain activated attapulgite;

[0025] B2, zirconium nitrate and 0.1 mol / L nitric acid aqueous solution are added to the reactor, stirred at room temperature until the system is dissolved, activated attapulgite is added to the reactor, stirred for 20-30 min, sodium hydroxide solution is added dropwise to the reactor, the pH of the reaction system is adjusted to 9-10, the temperature of the reactor is increased to 55-65°C, and the reactor is aged for 16-18 h, and the loaded attapulgite precursor is obtained by post-treatment;

[0026] B3, placing the loaded attapulgite precursor into a tubular furnace filled with oxygen, raising the temperature of the tubular furnace to 160-180°C, maintaining the temperature for 6-8 hours, cooling and discharging the material to obtain the loaded attapulgite;

[0027] B4. Add the loaded attapulgite, 3-aminopropyltriethoxysilane and anhydrous ethanol into a reactor and stir. Increase the temperature of the reactor to 50-60°C, add sodium hydroxide solution into the reactor, keep the temperature for 60-80 minutes, and post-treat to obtain modified attapulgite.

[0028] The synthetic reaction principle of modified attapulgite is:

[0029] Impurities on the surface of attapulgite can be removed by treating it with sodium hydroxide solution. As a strong base, sodium hydroxide has enhanced solubility at high temperature and can dissolve some silicate minerals on the surface and near the surface of attapulgite to form soluble silicate ions. The dissolution process is accompanied by slight etching of the attapulgite structure, which helps to open the originally closed or semi-closed pores and make the pore network more connected. The surface of attapulgite is rich in functional groups such as hydroxyl groups, which can undergo ion exchange reactions with sodium ions in the solution. Sodium ions occupy part of the surface of the attapulgite to form a more stable surface structure. At the same time, it also helps to further open the pores, increase the specific surface area and porosity of the active attapulgite, and provide more load for zirconium loading. sites, so that zirconium nitrate is ionized in water to produce zirconium ions which can be evenly loaded onto the activated attapulgite, thereby increasing the loading amount of lanthanum ions. Zirconium ions, as the central ions, form coordination bonds with ligands such as hydroxyl groups on the surface of attapulgite by adjusting the pH value of the reaction system, and promote the coordination reaction or electrostatic adsorption between zirconium ions and attapulgite, thereby increasing the loading amount and loading stability of zirconium ions on attapulgite. High-temperature oxidation treatment is then used to cause the zirconium ions to undergo an oxidation reaction to form zirconium oxide, thereby further consolidating the loading state of zirconium ions on the surface of attapulgite, promoting the interaction and interface bonding between attapulgite and zirconium oxide, and obtaining an attapulgite composite material with stably loaded zirconium oxide, i.e., loaded attapulgite.

[0030] Further, in step B1, the dosage ratio of the sodium hydroxide, 0.1 mol / L nitric acid aqueous solution and attapulgite is 3g:100mL:20g, and the post-treatment includes: after standing and aging, suction filtration, washing the filter cake with deionized water until neutral and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, vacuum drying to constant weight, crushing, and passing through a 200-mesh sieve to obtain activated attapulgite; in step B2, the dosage ratio of the zirconium nitrate, deionized water and activated attapulgite is 4g:100mL:15g, the concentration of the sodium hydroxide solution is 2-3mol / L, and the post-treatment includes: after aging is completed, the temperature of the reactor is lowered The reaction mixture is cooled to room temperature, filtered, the filter cake is washed with deionized water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain a loaded attapulgite precursor; in step B4, the amount ratio of the loaded attapulgite, 3-aminopropyltriethoxysilane, anhydrous ethanol and sodium hydroxide solution is 7g:3g:80mL:15mL, and the concentration of the sodium hydroxide solution is 2-3mol / L. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified attapulgite.

[0031] Furthermore, the preparation method of modified chitosan is as follows: chitosan and lanthanum nitrate aqueous solution are added to a reactor, stirred at room temperature for 30-50 minutes, glacial acetic acid is added to the reactor, the pH of the system is adjusted to 5-6, the temperature of the reactor is increased to 45-55°C, the mixture is stirred for 2-3 hours, and the modified chitosan is obtained by post-treatment.

[0032] The synthetic reaction principle of modified chitosan is:

[0033] The chitosan molecule has an amino or acetylamino group on C2 and a hydroxyl group on C3. From a conformational point of view, they are both flat bonds. Under weakly acidic conditions, lanthanum ions with a certain ionic radius coordinate and chelate with the hydroxyl and amino functional groups on the chitosan molecules to form a lanthanum-chitosan complex, thereby preparing modified chitosan with lanthanum chelated grafted chitosan.

[0034] Furthermore, the dosage ratio of the chitosan and the lanthanum nitrate aqueous solution is 1g:20mL, the concentration of the lanthanum nitrate aqueous solution is 0.05mol / L, the deacetylation degree of the chitosan is 85%, and the post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with deionized water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 65-75°C, vacuum drying to constant weight, crushing, and passing through a 200-mesh sieve to obtain modified chitosan.

[0035] The present invention has the following beneficial effects:

[0036] 1. The fluorine removal resin grafted with rare metal active groups of the present invention is a modified chitosan prepared by coordination and chelation of lanthanum and chitosan. Chitosan itself is a natural polysaccharide. After coordination and chelation of lanthanum, the positive charge and specific functional groups on its surface can enhance the affinity for fluoride ions. Lanthanum ions, as hard acids, have a strong coordination effect with fluoride ions, thereby improving the selective adsorption of fluoride ions. Attapulgite has a large specific surface area and pore structure. After loading zirconium oxide, its surface properties are further improved, and the adsorption sites for fluoride ions are increased. At the same time, the introduction of zirconium oxide may also enhance the adsorption capacity for fluoride ions through electrostatic action or surface complexation. Modified polyolefin microspheres are used as a skeleton and glutaraldehyde is used as a cross-linking agent to promote the cross-linking polymerization of modified chitosan and modified attapulgite in an emulsified system, so as to prepare a multi-particle cross-linked polymerized fluorine removal resin with selective adsorption of fluorine, further improving the porosity of the fluorine removal resin and increasing the adsorption capacity of the fluorine removal resin.

[0037] 2. The fluorine removal resin grafted with rare metal active groups of the present invention increases the specific surface area and porosity of attapulgite by sodiumizing attapulgite, so that zirconium can be fully loaded on the attapulgite in the form of ions, thereby increasing the loading amount of zirconium oxide in the modified attapulgite. The loading amount of zirconium oxide provides more adsorption sites, thereby enhancing the selective adsorption capacity of the fluorine removal resin for fluoride ions. In addition, zirconium oxide, as a highly stable material, enhances the chemical stability and thermal stability of the modified attapulgite and the entire fluorine removal resin, and helps to maintain the structural integrity and adsorption performance of the resin in multiple adsorption-desorption cycles. After chitosan is coordinated and chelated with lanthanum, the lanthanum ions in the modified chitosan have a high affinity with the fluoride ions and can form a stable coordination bond. This highly selective adsorption mechanism It ensures that fluoride ions are preferentially captured during the adsorption process, and reduces competitive adsorption with other coexisting anions, thereby improving the selective adsorption capacity and adsorption capacity of the defluorination resin for fluorine. During the desorption process, fluoride ions can be more easily and thoroughly removed from the resin without the need for complex desorption conditions or additional treatment steps. Lanthanum ions form stable coordination bonds with functional groups in chitosan molecules, thereby improving the stability of the entire molecule. This stability enables the modified chitosan to maintain its structure and performance stability under a wider pH range and temperature conditions, and cooperates with the modified attapulgite to enable the defluorination resin to maintain the structural integrity of the resin during multiple adsorption-desorption cycles, thereby maintaining the adsorption performance of the resin, preventing performance degradation due to structural damage, and extending the cycle life of the defluorination resin.

[0038] 3. The fluorine-removing resin grafted with rare metal active groups of the present invention is modified by using glycidyl methacrylate and divinylbenzene as monomers and then subjecting them to free radical polymerization in an emulsification system to prepare modified polyolefin microspheres with a porous structure modified by multiple hydroxyls. Fluoride ions are highly electronegative ions with a strong ability to attract electrons and can form hydrogen bonds with hydrogen atoms in functional groups such as hydroxyl groups on the modified polyolefin microspheres, so that the fluoride ions can be tightly bound to the surface or inside of the microspheres, thereby improving the selective adsorption capacity of the microspheres for fluoride ions. The pore structure of the modified polyolefin microspheres not only provides more adsorption sites for fluoride ion adsorption, but also promotes the diffusion and transmission of fluoride ions in the resin. The modified polyolefin microspheres, modified chitosan and modified attapulgite cooperate with each other to further improve the selective adsorption capacity of the fluorine-removing resin for fluorine, so that the fluorine-removing resin exhibits good fluorine adsorption performance and recycling regeneration performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 is the infrared spectrum of the modified chitosan in the present invention;

[0041] Figure 2 This is the XRD diagram of the loaded attapulgite in the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing a fluorine-removing resin grafted with rare metal active groups, comprising the following steps:

[0045] S1. Preparation of loaded attapulgite

[0046] Weigh: 30 g of sodium hydroxide and 1000 mL of deionized water are added to a reactor, stirred at room temperature until the system is dissolved, 200 g of attapulgite is added to the reactor, the temperature of the reactor is raised to 70°C, and the mixture is stirred for 2 hours. The temperature of the reactor is lowered to room temperature, and the mixture is aged for 20 hours. The filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 70°C, vacuum dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain activated attapulgite.

[0047] Weigh: add 80g of zirconium nitrate and 2000mL of 0.1mol / L nitric acid aqueous solution into a reactor, stir at room temperature until the system is dissolved, add 300g of activated attapulgite into the reactor, stir for 20min, drop 2mol / L sodium hydroxide solution into the reactor, adjust the pH of the reaction system to 9, increase the temperature of the reactor to 55°C, keep warm and age for 16h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water until it is neutral and then dry, transfer the filter cake to a drying oven at 70°C, dry to constant weight, and obtain a loaded attapulgite precursor;

[0048] The loaded attapulgite precursor was placed in a tubular furnace. In an environment where the oxygen atmosphere concentration was 60 vol%, the temperature of the tubular furnace was raised to 160°C, and the temperature was kept for 6 hours. The material was cooled and discharged to obtain the loaded attapulgite.

[0049] S2. Preparation of modified attapulgite

[0050] Weigh: 280 g of loaded attapulgite, 120 g of 3-aminopropyltriethoxysilane and 3200 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 50 ° C, add 600 mL of 2 mol / L sodium hydroxide solution into the reactor, keep warm for 60 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until neutral, transfer the filter cake to a drying oven at a temperature of 60 ° C, dry to constant weight, and obtain modified attapulgite.

[0051] S3. Preparation of modified polyolefin microspheres

[0052] Weigh: 50 g of glycidyl methacrylate, 40 g of p-divinylbenzene, 1 g of azobisisobutyronitrile and 500 mL of toluene, add them into a reactor and stir, raise the temperature of the reactor to 70° C., keep the temperature for 6 hours, and then lower the temperature to room temperature to obtain a polyolefin reaction liquid;

[0053] Ethanol, purified water, polyethylene glycol, sodium dodecyl sulfate, and Tween-80 were mixed uniformly in a dosage ratio of 50 mL: 30 mL: 3 g: 2 g: 2 g to obtain an emulsified solution;

[0054] The emulsified solution was added to the reactor, and the stirring speed was set to 550 r / min at room temperature. The polyolefin reaction solution was added dropwise to the reactor. After the addition was completed, the mixture was stirred for 30 minutes under heat preservation, and the mixture was filtered. The filter cake was washed with anhydrous ethanol for 3 times and then dried. The filter cake was transferred to a drying oven at a temperature of 60° C. and vacuum dried to constant weight to obtain polyolefin microspheres, wherein the volume ratio of the emulsified solution to the polyolefin reaction solution was 2:1.

[0055] Weigh: 60 g of gulose, 600 mL of purified water, and 40 g of sodium hydroxide, add them to the reactor, stir until the system is dissolved, add 100 g of polyolefin microspheres to the reactor, raise the temperature of the reactor to 50°C, keep the reaction for 2 hours, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at 60°C, and vacuum dry to constant weight to obtain modified polyolefin microspheres.

[0056] S4. Preparation of modified chitosan

[0057] Weigh: 10 g of chitosan with a deacetylation degree of 85% and 200 mL of a 0.05 mol / L lanthanum nitrate aqueous solution, add them to a reactor, stir at room temperature for 30 min, add glacial acetic acid to the reactor, adjust the system pH to 5, raise the reactor temperature to 45°C, keep stirring for 2 h, filter, wash the filter cake with deionized water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified chitosan.

[0058] S5. Preparation of fluorine removal resin

[0059] Toluene, tetrahydrofuran, purified water, polyethylene glycol 400, OP-20, and Tween-80 were uniformly mixed in a dosage ratio of 40 mL: 40 mL: 30 mL: 10 g: 3 g: 2 g to obtain an emulsion;

[0060] Weigh: 90g of modified attapulgite, 56g of modified chitosan, 36g of modified polyolefin microspheres, and 1400mL of emulsion are added to the reactor and stirred. 2mol / L sodium hydroxide solution is added dropwise to the reactor to adjust the pH of the system to 9. The temperature of the reactor is raised to 50°C. 240mL of 50wt% glutaraldehyde solution is added to the reactor and the reaction is kept warm for 4h. 2800mL of petroleum ether is added to the reactor and stirred for 30min. The temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed 5 times with anhydrous ethanol and then washed 3 times with deionized water. After drying, the filter cake is transferred to a drying oven at 55°C and vacuum dried to constant weight to obtain a defluorination resin.

[0061] Example 2

[0062] This embodiment provides a method for preparing a fluorine-removing resin grafted with rare metal active groups, comprising the following steps:

[0063] S1. Preparation of loaded attapulgite

[0064] Weigh: 30 g of sodium hydroxide and 1000 mL of deionized water are added to a reactor, stirred at room temperature until the system is dissolved, 200 g of attapulgite is added to the reactor, the temperature of the reactor is raised to 75°C, and the mixture is stirred for 2.5 hours. The temperature of the reactor is lowered to room temperature, and the mixture is aged for 22 hours. The filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 75°C, vacuum dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain activated attapulgite.

[0065] Weigh: add 80g of zirconium nitrate and 2000mL of 0.1mol / L nitric acid aqueous solution into a reactor, stir at room temperature until the system is dissolved, add 300g of activated attapulgite into the reactor, stir for 25min, drop 2.5mol / L sodium hydroxide solution into the reactor, adjust the pH of the reaction system to 9.5, increase the temperature of the reactor to 60°C, keep warm and age for 17h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water until it is neutral and then drain, transfer the filter cake to a drying oven at 75°C, dry to constant weight, and obtain a loaded attapulgite precursor;

[0066] The loaded attapulgite precursor was placed in a tubular furnace. In an environment where the oxygen atmosphere concentration was 70 vol%, the temperature of the tubular furnace was increased to 170°C, and the temperature was kept for 7 hours. The material was cooled and discharged to obtain the loaded attapulgite.

[0067] S2. Preparation of modified attapulgite

[0068] Weigh: 280 g of loaded attapulgite, 120 g of 3-aminopropyltriethoxysilane and 3200 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 55 ° C, add 600 mL of 2.5 mol / L sodium hydroxide solution into the reactor, keep warm for 70 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until neutral, transfer the filter cake to a drying oven at a temperature of 65 ° C, dry to constant weight, and obtain modified attapulgite.

[0069] S3. Preparation of modified polyolefin microspheres

[0070] Weigh: 50 g of glycidyl methacrylate, 40 g of p-divinylbenzene, 1 g of azobisisobutyronitrile and 500 mL of toluene, add into a reactor and stir, raise the temperature of the reactor to 75° C., keep the temperature for 7 hours, and then lower the temperature to room temperature to obtain a polyolefin reaction liquid;

[0071] Ethanol, purified water, polyethylene glycol, sodium dodecyl sulfate, and Tween-80 were mixed uniformly in a dosage ratio of 50 mL: 30 mL: 3 g: 2 g: 2 g to obtain an emulsified solution;

[0072] The emulsified solution was added to the reactor. At room temperature, the stirring speed was set to 575 r / min. The polyolefin reaction solution was added dropwise to the reactor. After the addition was completed, the mixture was stirred for 4 minutes under heat preservation. The mixture was filtered by suction. The filter cake was washed with anhydrous ethanol for 3 times and then dried. The filter cake was transferred to a drying oven at a temperature of 65° C. and vacuum dried to constant weight to obtain polyolefin microspheres. The volume ratio of the emulsified solution to the polyolefin reaction solution was 2:1.

[0073] Weigh: 60 g of gulose, 600 mL of purified water, and 40 g of sodium hydroxide, add them to the reactor, stir until the system is dissolved, add 100 g of polyolefin microspheres to the reactor, raise the temperature of the reactor to 55°C, keep the reaction warm for 2.5 hours, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry to constant weight to obtain modified polyolefin microspheres.

[0074] S4. Preparation of modified chitosan

[0075] Weigh: 10 g of chitosan with a deacetylation degree of 85% and 200 mL of a 0.05 mol / L lanthanum nitrate aqueous solution, add them to a reactor, stir at room temperature for 40 min, add glacial acetic acid to the reactor, adjust the system pH to 5.5, raise the reactor temperature to 50°C, keep warm and stir for 2.5 h, filter, wash the filter cake with deionized water until it is neutral and then drain, transfer the filter cake to a drying oven at 70°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified chitosan.

[0076] S5. Preparation of fluorine removal resin

[0077] Toluene, tetrahydrofuran, purified water, polyethylene glycol 400, OP-20, and Tween-80 were uniformly mixed in a dosage ratio of 40 mL: 40 mL: 30 mL: 10 g: 3 g: 2 g to obtain an emulsion;

[0078] Weigh: 95g of modified attapulgite, 60g of modified chitosan, 40g of modified polyolefin microspheres, and 1400mL of emulsion, add them to the reactor and stir, add 2.5mol / L sodium hydroxide solution dropwise to the reactor, adjust the system pH to 9.5, raise the temperature of the reactor to 55°C, add 280mL of 50wt% glutaraldehyde solution to the reactor, keep warm and react for 5h, add 2800mL of petroleum ether to the reactor, keep warm and stir for 40min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 5 times, wash it with deionized water 3 times, drain it, transfer the filter cake to a drying oven at 60°C, and vacuum dry it to constant weight to obtain a defluorination resin.

[0079] Example 3

[0080] This embodiment provides a method for preparing a fluorine-removing resin grafted with rare metal active groups, comprising the following steps:

[0081] S1. Preparation of loaded attapulgite

[0082] Weigh: 30 g of sodium hydroxide and 1000 mL of deionized water are added to a reactor, stirred at room temperature until the system is dissolved, 200 g of attapulgite is added to the reactor, the temperature of the reactor is raised to 80°C, and the mixture is stirred for 3 hours. The temperature of the reactor is lowered to room temperature, and the mixture is allowed to stand for aging for 24 hours. The filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 80°C, vacuum dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain activated attapulgite.

[0083] Weigh: add 80g of zirconium nitrate and 2000mL of 0.1mol / L nitric acid aqueous solution into a reactor, stir at room temperature until the system is dissolved, add 300g of activated attapulgite into the reactor, stir for 30min, drop 3mol / L sodium hydroxide solution into the reactor, adjust the pH of the reaction system to 10, increase the temperature of the reactor to 65°C, keep warm and age for 18h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water until it is neutral and then drain, transfer the filter cake to a drying oven at 80°C, dry to constant weight, and obtain a loaded attapulgite precursor;

[0084] The loaded attapulgite precursor was placed in a tubular furnace. In an environment where the oxygen atmosphere concentration was 80 vol%, the temperature of the tubular furnace was raised to 180°C, and the temperature was kept for 8 hours. The material was cooled and discharged to obtain the loaded attapulgite.

[0085] S2. Preparation of modified attapulgite

[0086] Weigh: 280 g of loaded attapulgite, 120 g of 3-aminopropyltriethoxysilane and 3200 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 60°C, add 600 mL of 3 mol / L sodium hydroxide solution into the reactor, keep warm and react for 80 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, transfer the filter cake to a drying oven at a temperature of 70°C, dry to constant weight, and obtain modified attapulgite.

[0087] S3. Preparation of modified polyolefin microspheres

[0088] Weigh: 50 g of glycidyl methacrylate, 40 g of p-divinylbenzene, 1 g of azobisisobutyronitrile and 500 mL of toluene, add them into a reactor and stir, raise the temperature of the reactor to 80° C., keep the temperature for reaction for 8 hours, and then lower the temperature to room temperature to obtain a polyolefin reaction liquid;

[0089] Ethanol, purified water, polyethylene glycol, sodium dodecyl sulfate, and Tween-80 were mixed uniformly in a dosage ratio of 50 mL: 30 mL: 3 g: 2 g: 2 g to obtain an emulsified solution;

[0090] Add the emulsified solution to the reactor, set the stirring speed to 600 r / min at room temperature, add the polyolefin reaction solution dropwise to the reactor, keep warm and stir for 50 minutes after the addition is completed, filter, wash the filter cake with anhydrous ethanol three times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry to constant weight to obtain polyolefin microspheres, wherein the volume ratio of the emulsified solution to the polyolefin reaction solution is 2:1;

[0091] Weigh: 60 g of gulose, 600 mL of purified water, and 40 g of sodium hydroxide, add them into a reactor, stir until the system is dissolved, add 100 g of polyolefin microspheres into the reactor, raise the temperature of the reactor to 60°C, keep the reaction warm for 3 hours, lower the temperature of the reactor to room temperature, filter, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain modified polyolefin microspheres.

[0092] S4. Preparation of modified chitosan

[0093] Weigh: 10 g of chitosan with a deacetylation degree of 85% and 200 mL of a 0.05 mol / L lanthanum nitrate aqueous solution, add them to a reactor, stir at room temperature for 50 min, add glacial acetic acid to the reactor, adjust the system pH to 6, raise the reactor temperature to 55°C, keep stirring for 3 h, filter, wash the filter cake with deionized water until it is neutral and then drain, transfer the filter cake to a drying oven at 75°C, vacuum dry to constant weight, crush, and pass through a 200-mesh sieve to obtain modified chitosan.

[0094] S5. Preparation of fluorine removal resin

[0095] Toluene, tetrahydrofuran, purified water, polyethylene glycol 400, OP-20, and Tween-80 were uniformly mixed in a dosage ratio of 40 mL: 40 mL: 30 mL: 10 g: 3 g: 2 g to obtain an emulsion;

[0096] Weigh: 100g of modified attapulgite, 64g of modified chitosan, 44g of modified polyolefin microspheres, and 1400mL of emulsion are added to the reactor and stirred. 3mol / L sodium hydroxide solution is added dropwise to the reactor to adjust the pH of the system to 10. The temperature of the reactor is raised to 60°C. 320mL of 50wt% glutaraldehyde solution is added to the reactor and the reaction is kept warm for 6h. 2800mL of petroleum ether is added to the reactor and stirred for 50min. The temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed 5 times with anhydrous ethanol, washed 3 times with deionized water, dried, and the filter cake is transferred to a drying oven at 65°C and vacuum dried to constant weight to obtain a defluorination resin.

[0097] Comparative Example 1

[0098] The difference between this comparative example and Example 3 is that in step S1, attapulgite is used instead of activated attapulgite to prepare the loaded attapulgite precursor.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 3 is that the modified polyolefin microspheres in step S5 are replaced by polyolefin microspheres in step S3.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 3 is that step S4 is eliminated, and the chitosan in step S4 is substituted for the modified chitosan in step S5.

[0103] Performance Testing:

[0104] Sodium fluoride and sodium hydroxide were dissolved in drinking water to prepare a pH of 8 and a fluoride content of 15 mg / L (W f0 ) as fluorine-containing wastewater, the defluorination resin prepared in Example 1-3 and Comparative Example 1-3 as a sample, weigh 100g of the sample and 10L of fluorine-containing wastewater into a rubber bucket, stir at room temperature for 24h, and measure the fluorine content W in the fluorine-containing wastewater. f1 , the sample was regenerated and desorbed using an acidic aqueous solution. After repeating the operation ten times, 100 g of the sample after 10 cycles was put into 10 L, pH = 8, and the fluorine content was 15 mg / L (W f0 ) in fluorine-containing wastewater, stirred at room temperature for 24 hours, and the fluorine content in the fluorine-containing wastewater was determined. f2 , and according to the formula Calculate the initial adsorption capacity δ1 of the defluorination resin and the adsorption capacity δ2 after 10 cycles, where W0 = 15 g / L, W f W f1 or W f2 , V 废水 is the volume of fluorine-containing wastewater (10L), M is the weight of the sample, and the specific test results are shown in Table 1 below.

[0105] Table 1-Performance test data of the sample

[0106]

[0107]

[0108] Performance Testing:

[0109] A comparative analysis of the data in Table 1 above shows that the first adsorption capacity of fluorine in fluorine-containing wastewater prepared by the present invention reaches 1.229 mg / g. After 10 cycles of adsorption, the adsorption capacity of fluorine in fluorine-containing wastewater by the fluorine-removing resin reaches 1.095, and the adsorption retention of fluorine in fluorine-containing wastewater by the fluorine-removing resin reaches 89.1%. All performance references are better than those of the comparative examples, indicating that the present invention uses modified polyolefin microspheres as a skeleton and glutaraldehyde as a cross-linking agent to promote the cross-linking polymerization of modified chitosan and modified attapulgite in an emulsified system to prepare a multi-particle cross-linked polymerized fluorine-removing resin with high selective adsorption of fluorine, which not only effectively improves the adsorption capacity of fluorine in wastewater by the fluorine-removing resin, but also improves the recycling and regeneration ability of the fluorine-removing resin, thereby extending the cycle service life of the fluorine-removing resin.

[0110] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0111] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0112] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A fluorine-removing resin grafted with rare metal active groups, characterized in that: The invention comprises the following components in parts by weight: 45-50 parts of modified attapulgite, 28-32 parts of modified chitosan, 18-22 parts of modified polyolefin microspheres and 60-80 parts of glutaraldehyde; Modified polyolefin microspheres are processed by the following steps: A1. Add glycidyl methacrylate, p-divinylbenzene, initiator and toluene into a reaction kettle and stir. Raise the temperature of the reaction kettle to 70-80° C., keep the temperature for 6-8 hours, and then lower the temperature to room temperature to obtain a polyolefin reaction liquid. A2, add the emulsified solution into the reactor, stir rapidly at room temperature, add the polyolefin reaction solution dropwise into the reactor, and after the addition is complete, keep warm and stir for 30-50 minutes, and perform post-treatment to obtain polyolefin microspheres; A3, adding gulose, purified water and sodium hydroxide into a reactor, stirring until the system is dissolved, adding polyolefin microspheres into the reactor, raising the temperature of the reactor to 50-60°C, keeping the temperature for reaction for 2-3h, and post-treating to obtain modified polyolefin microspheres; Modified attapulgite is obtained by the following steps: B1. Add sodium hydroxide and deionized water to a reactor, stir at room temperature until the system is dissolved, add attapulgite to the reactor, increase the temperature of the reactor to 70-80°C, keep stirring for 2-3 hours, lower the temperature of the reactor to room temperature, let it stand for aging for 20-24 hours, and post-treat to obtain activated attapulgite; B2, zirconium nitrate and 0.1 mol / L nitric acid aqueous solution are added to the reactor, stirred at room temperature until the system is dissolved, activated attapulgite is added to the reactor, stirred for 20-30 min, sodium hydroxide solution is added dropwise to the reactor, the pH of the reaction system is adjusted to 9-10, the temperature of the reactor is increased to 55-65°C, and the reactor is aged for 16-18 h, and the loaded attapulgite precursor is obtained by post-treatment; B3, placing the loaded attapulgite precursor into a tubular furnace filled with oxygen, raising the temperature of the tubular furnace to 160-180°C, maintaining the temperature for 6-8 hours, cooling and discharging the material to obtain the loaded attapulgite; B4, adding loaded attapulgite, 3-aminopropyltriethoxysilane and anhydrous ethanol into a reactor and stirring, raising the temperature of the reactor to 50-60° C., adding sodium hydroxide solution into the reactor, keeping the temperature for reaction for 60-80 min, and post-treating to obtain modified attapulgite; The preparation method of modified chitosan is as follows: chitosan and lanthanum nitrate aqueous solution are added to a reactor, stirred at room temperature for 30-50 minutes, glacial acetic acid is added to the reactor, the pH value of the system is adjusted to 5-6, the temperature of the reactor is increased to 45-55°C, the temperature is kept and stirred for 2-3 hours, and the modified chitosan is obtained by post-treatment; The preparation method of the defluorination resin comprises the following steps: adding modified attapulgite, modified chitosan, modified polyolefin microspheres and emulsion into a reaction kettle and stirring, dropping a sodium hydroxide solution into the reaction kettle, adjusting the pH value of the system to 9-10, raising the temperature of the reaction kettle to 50-60° C., adding a glutaraldehyde solution into the reaction kettle, keeping the temperature for reaction for 4-6 hours, adding petroleum ether into the reaction kettle, keeping the temperature for stirring for 30-50 minutes, and performing post-treatment to obtain the defluorination resin.

2. The fluorine-removing resin grafted with rare metal active groups according to claim 1, characterized in that: The modified attapulgite, emulsion and petroleum ether are used in a ratio of 45-50g:700mL:1400mL, the mass fraction of the glutaraldehyde solution is 50%, the concentration of the sodium hydroxide solution is 2-3mol / L, the emulsion is composed of toluene, tetrahydrofuran, purified water, polyethylene glycol 400, OP-20, and Tween-80 in a ratio of 40mL:40mL:30mL:10g:3g:2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with anhydrous ethanol for 5 times, and then washed with deionized water for 3 times, and then dried, and the filter cake is transferred to a drying oven at a temperature of 55-65°C, and vacuum dried to constant weight to obtain a defluorination resin.

3. The defluorination resin grafted with rare metal active groups according to claim 1, characterized in that: In step A1, the amount ratio of glycidyl methacrylate, p-divinylbenzene, initiator and toluene is 5g:4g:0.1g:50mL, and the initiator is azobisisobutyronitrile; in step A2, the volume ratio of the emulsified solution and the polyolefin reaction solution is 2:1, and the emulsified solution is composed of ethanol, purified water, polyethylene glycol, sodium dodecyl sulfate, and Tween-80 in an amount ratio of 50mL:30mL:3g:2g:2g, and the post-treatment includes: after the reaction is completed, Filter by suction, wash the filter cake with anhydrous ethanol for 3 times and then drain it, transfer the filter cake to a drying oven at a temperature of 60-70°C, and vacuum dry it to constant weight to obtain polyolefin microspheres; in step A3, the amount ratio of gulose, purified water, sodium hydroxide and polyolefin microspheres is 3g:30mL:2g:5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filter by suction, transfer the filter cake to a drying oven at a temperature of 60-70°C, and vacuum dry it to constant weight to obtain modified polyolefin microspheres.

4. The fluorine-removing resin grafted with rare metal active groups according to claim 1, characterized in that: In step B1, the dosage ratio of sodium hydroxide, deionized water and attapulgite is 3g:100mL:20g, and the post-treatment includes: after standing aging, suction filtration, washing the filter cake with deionized water until neutral and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, vacuum drying to constant weight, crushing, and passing through a 200-mesh sieve to obtain activated attapulgite; in step B2, the dosage ratio of zirconium nitrate, 0.1mol / L nitric acid aqueous solution and activated attapulgite is 4g:100mL:15g, the concentration of the sodium hydroxide solution is 2-3mol / L, and the post-treatment includes: after aging is completed, the temperature of the reactor is reduced to room temperature Temperature, filter, wash the filter cake with deionized water until neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70-80°C, dry to constant weight, and obtain a loaded attapulgite precursor; in step B4, the amount ratio of the loaded attapulgite, 3-aminopropyltriethoxysilane, anhydrous ethanol and sodium hydroxide solution is 7g:3g:80mL:15mL, the concentration of the sodium hydroxide solution is 2-3mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filter, wash the filter cake with purified water until neutral, transfer the filter cake to a drying oven at a temperature of 60-70°C, dry to constant weight, and obtain modified attapulgite.

5. The fluorine-removing resin grafted with rare metal active groups according to claim 1, characterized in that: The dosage ratio of the chitosan and the lanthanum nitrate aqueous solution is 1g:20mL, the concentration of the lanthanum nitrate aqueous solution is 0.05mol / L, the deacetylation degree of the chitosan is 85%, and the post-treatment comprises: after the reaction is completed, suction filtration, washing the filter cake with deionized water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 65-75°C, vacuum drying to constant weight, crushing, and passing through a 200-mesh sieve to obtain modified chitosan.

Citation Information

Patent Citations

  • High-efficiency fluorine removal agent for wastewater as well as preparation method and use method of high-efficiency fluorine removal agent

    CN117563685A

  • Modified chitosan crosslinked resin for defluorination in water and method of preparing the same

    CN101249422A

  • Preparation method of ethylenediamine tetraacetic acid modified magnetic attapulgite-chitosan microspheres

    CN111282551A